Baseline platelet count in percutaneous coronary intervention: a dose–response meta-analysis. Issue 22 (25th May 2022) - Galimzhanov, Akhmetzhan; Sabitov, Yersyn; Tenekecioglu, Erhan; Tun, Han Naung; Alasnag, Mirvat; Mamas, Mamas A
Abstract : Objectives: The nature of the relationship between baseline platelet count and clinical outcomes following percutaneous coronary intervention (PCI) is unclear. We undertook dose–response and pairwise meta-analyses to better describe the prognostic value of the initial platelet count and clinical endpoints in patients after PCI. Methods: A search of PubMed, Scopus and Web of Science (up to 9 October 2021) was performed to identify studies that evaluated the association between platelet count and clinical outcomes following PCI. The primary outcomes of interest were all-cause mortality, major adverse cardiovascular events (MACE) and major bleeding. We performed random-effects pairwise and one-stage dose–response meta-analyses by calculating HRs and 95% CIs. Results: The meta-analysis included 19 studies with 217 459 patients. We report a J-shaped relationship between baseline thrombocyte counts and all-cause death, MACE and major bleeding at follow-up. The risk of haemorrhagic events exceeded the risk of thrombotic events at low platelet counts (<175×10 9 /L), while a predominant ischaemic risk was observed at high platelet counts (>250×10 9 /L). Pairwise meta-analyses revealed a robust link between initial platelet counts and the risk of postdischarge all-cause mortality, major bleeding (for thrombocytopenia: HR 1.39, 95% CI 1.30 to 1.49; HR 1.51, 95% CI 1.15 to 2.00, respectively) and future death from any cause and MACE (thrombocytosis: HR 1.60, 95% CI 1.29 to 1.98; HR 1.47, 95% CI 1.22 to 1.78, respectively). Conclusion: Low platelet counts were associated with the predominant bleeding risk, while high platelet counts were only associated with the ischaemic events. PROSPERO registration number: CRD42021283270.